2008
DOI: 10.1002/cbic.200800213
|View full text |Cite
|
Sign up to set email alerts
|

But‐3‐ene‐1,2‐diol: A Mechanism‐Based Active Site Inhibitor for Coenzyme B12‐Dependent Glycerol Dehydratase

Abstract: Coenzyme B(12)-dependent glycerol dehydratase is a radical enzyme that catalyses the conversion of glycerol into 3-hydroxypropanal and propane-1,2-diol into propanal via enzyme-bound intermediate radicals. The substrate analogue but-3-ene-1,2-diol was studied in the expectation that it would lead to the 4,4-dihydroxylbut-2-en-1-yl radical, which is stabilised (allylic) and not reactive enough to retrieve a hydrogen atom from 5'-deoxyadenosine, thereby interrupting the catalytic cycle. Racemic and enantiomerica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…[13] However, additional EPR studies with GDH and selectively deuterated but-3-ene-1,2-diols ( [ ]) suggested that the spin density during GDH inactivation is concentrated close to the C1 atom, rather than the C2 or C4 atoms. [10] This result was interpreted to indicate a build-up of the 1,2-dihydroxybut-3-en-1-yl radical (8). Relative to 9, however, 8 does not appear to possess any functionality that would render it particularly stable.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…[13] However, additional EPR studies with GDH and selectively deuterated but-3-ene-1,2-diols ( [ ]) suggested that the spin density during GDH inactivation is concentrated close to the C1 atom, rather than the C2 or C4 atoms. [10] This result was interpreted to indicate a build-up of the 1,2-dihydroxybut-3-en-1-yl radical (8). Relative to 9, however, 8 does not appear to possess any functionality that would render it particularly stable.…”
Section: Introductionmentioning
confidence: 84%
“…[10] It was found that DDH was also inactivated by the 3-unA C H T U N G T R E N N U N G sat-A C H T U N G T R E N N U N G urated diol in an EPR-active and time-dependent fashion. The identification of Ado À H by HPLC analysis implies that hydrogen abstraction from 7 did take place (step A in Equation (2)).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations